Photophysiological Responses of Canopy-Forming Kelp Species to Short-Term Acute Warming - Burdett, Heidi L.; Wright, Honor; Smale, Dan A. (Frontiers in Marine Science, 2019)
The frequency of short-term oceanic warming events (‘marine heatwaves’ [MHWs] or heat spikes) has increased over the past century and is projected to further increase because of anthropogenic climate change. Given that marine organisms are strongly influenced by temperature, an increased occurrence of warming events could alter the structure of populations, communities and ecosystems. The distribution and ecophysiological performance of kelp species – globally important foundation species that play significant roles in nutrient cycling and habitat creation in temperate coastal systems – is particularly constrained by temperature. However, their photophysiological responses to warming events remains unclear, which hinders attempts to understand and predict the effects of ocean warming on kelp populations and the ecosystems they underpin. Here, we experimentally simulated a heat spike (+2°C and +4°C in magnitude, 3 days in duration, compared with ambient controls) and examined the photophysiological responses of two canopy-forming kelp species widely distributed across the northeast Atlantic - Laminaria digitata and L. hyperborea. Both species were resilient to the realistic warming treatments in terms of their photosynthetic characteristics. However, we found that L. digitata individuals, which were collected from populations found towards the upper limit of this species’ thermal range, exhibited increased oxygen production at higher temperatures, particularly after multiple days of exposure to the warming event. Laminaria digitata also exhibited a greater poise for dissipating excess energy through non-photochemical pathways. In contrast, L. hyperborea, which extends further south into warmer waters and tends to occupy deeper reefs that are almost constantly submerged, appeared to be photo-physiologically insensitive to the heat spike. This study enhances our mechanistic understanding of the photophysiological and photoprotective responses of kelps to short-term acute warming events – features which are likely to emerge as important drivers of ecological change in coming decades.